Validation, Invalidation, and Negative Speech Acts in Dementia Care Discourse - Amino, Kaoru (Frontiers in Communication, 2020)
In line with Japan’s growing elderly population, interdisciplinary research into gerontology and dementia is expanding into its own specialization. Neo-gerontology, ageism, and other generative research fields require coordination between medical care providers, pharmaceutical intervention, and communication modalities that help cope with the complex issues presented by dementia. In this study, discourse during dementia care in Japan is analyzed from an interdisciplinary perspective. Since some elements of dementia care are best described through the lens of discourse analysis, theoretical concepts borrowed from applied linguistics and communication studies provide practical tools to caregivers in monitoring and developing themselves professionally. Oches (2002), for example, finds that intersubjective, stereotypical views towards autistic students are analogous to the typical view of dementia PTs as senile, pitiful, and weak, demonstrating the natural extension of linguistic and communication theories to the setting of dementia care. Validation (Feil, 2001) and invalidation (Wheert, et,al, 2008) are scales used to gauge caregiver attitude towards PTs and are based on theories of individual schema, frame, and PT subjectivity. As a theoretical framework, pragmatic expressions that convey intersubjectivity and subjectivity as related to validation and invalidation are examined among both PTs and caregivers based on transcripts of encounters that took place in a Japanese hospital examination rooms among physicians, caregivers, and dementia PTs (N ＝17) in 2016. Consequently, invalidation, which is attributed to the constructed subjectivity of PTs by caregivers, can be observed as 1) representations of PT thoughts, emotions, or senses, 2) representations of intention by some utterance or action, 3) requests for reorientation towards reality, 4) accusations of misunderstanding related to memory loss, and 5) testing of cognitive elements. This framework therefore implies that the necessity of separating caregiver interpretations from those of the PTs is key to understanding functional communication in dementia discourse.